PENINGKATAN EFISIENSI BIAYA DENGAN ANALISIS VALUE CHAIN PADA USAHA BATIK TANAH LIEK KOTO BARU, KABUPATEN SOLOK, SUMATERA BARAT - Elsa Meirina; Mike Kusuma Dewi; Melfia Melfia (Jurnal Abdimas Bina Bangsa, 2023)
One of the handicraft industries in West Sumatra that is currently being activated is the development of the batik industry. One of the developing batik industries is the Tanah Liek batik industry. With the development of the batik industry, the right strategy is needed so that the batik produced has an added value (value) chain in the eyes of consumers. This service activity provides appropriate counseling so that batik craftsmen, especially Tanah Liek batik in the city of Solok, can provide a value chain that has an impact on the profits of batik craftsmen later. Not only the design of the batik pattern that will be highlighted but also the price and quality of the durable product which will be a competitive advantage against other types of batik. The community service activities carried out by the team of lecturers and students aim to provide the right direction in improving profit oriented to the product value chain, namely Tanah Liek batik